Simplified model for the non-linear behaviour representation of reinforced concrete columns under biaxial bending - Rodrigues, H. (2013)
In the present paper a simplified model is proposed for the force-deformation behaviour of reinforced concrete members under biaxial loading combined with axial force. The starting point for the model development was an existing fixed-length plastic hinge element model that accounts for the non-linear hysteretic behaviour at the element end-sections, characterized by trilinear moment-curvature laws. To take into account the section biaxial behaviour, the existing model was adopted for both orthogonal lateral directions and an interaction function was introduced to couple the hysteretic response of both directions. To calibrate the interaction function it were used numerical results, obtained from fibre models, and experimental results. For the parameters identification, non-linear optimization approaches were adopted, namely: the gradient based methods followed by the genetic, evolutionary and nature-inspired algorithms. Finally, the simplified non-linear model proposed is validated through the analytical simulation of biaxial test results carried out in full-scale reinforced concrete columns.